MOTIVASI HIJRAH MILENIAL MUSLIM PERKOTAAN MELALUI DAKWAH DIGITAL (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2020)
Abstract. This research increases motivation for millennial youth emigration through digital propaganda. By looking at the fact that young people today are familiar with the word hijrah and social media, but not all users use social media as a tool to emigrate. People only know the meaning of migrating without applying it in everyday life. In addition, with the advancement of technology can make the propaganda model more interesting, developing fast and dynamic. Researchers use descriptive qualitative and literature studies through questionnaires, then collect information from journals, books and online media, it is hoped that this can provide information about the motivation of young people to emigrate. The results of this study proved that using digital propaganda can increase the motivation of the hijrah youth millennial, judging from the results of the questionnaire stated 72% the use of digital media in the spread of da'wah it’s optimal. Keywords: motivation, youth migrate, digital propaganda